Prevalence and Associated Factors of Sexual Dysfunction in Patients With Inflammatory Bowel Disease - Zhang, Jinzhi; Nie, Jiao; Zou, Min; Zeng, Qishan; Feng, Yue; Luo, Zhenyi; Gan, Huatian (Frontiers in Endocrinology, 2022)
Background: Sexual dysfunction (SD) in patients who suffer from inflammatory bowel disease (IBD) has not attracted widespread attention, and thus research studies are scarce. Objective: This study aims to evaluate the rates of SD in IBD compared with healthy individuals and elucidate the associated factors. Methods: In this cross-sectional study, the Female Sexual Function Index (FSFI) and the simplified version of the International Index of Erectile Function (IIEF-5) were filled by IBD patients, as well as healthy control individuals. Results: A total of 208 IBD patients, including 133 with Crohn's disease (CD) and 75 with ulcerative colitis (UC) , and 190 healthy individuals filled out the questionnaires. In women, SD rates were 61.9% in the patients with IBD vs. 24.4% in the healthy controls (p < 0.01). In men, the rates of erectile dysfunction (ED) were 43.5% in the patients with IBD vs. 12.5% in the healthy controls (p < 0.01). Anxiety (OR, 3.092; 95%CI: 1.033-9.252, p = 0.044) and active perianal disease (OR, 4.481; 95%CI: 1.055-19.029, p = 0.042) were independent risk factors for SD in female IBD patients. age (OR, 1.050; 95%CI: 1.007-1.095, p = 0.022), depression (OR, 5.763; 95%CI: 1.864-17.821, p = 0.002) and active perianal disease (OR, 7.117; 95%CI: 1.747-28.983, p = 0.006) were independent risk factors for ED in male patients. Conclusions: In the IBD patients, 62% of women reported having SD, and 44% of men reported having ED. These higher rates, as compared to the healthy controls, are mostly driven by active perianal disease and psychological factors.